Religious Orientation and The Understanding of Free Will Among Theology Students: A Religious Psychology Perspective - Simaremare, Elkana Anggi Maranata; Ranimpi, Yulius Yusak; Tampake, Tony (IAIN Palangka Raya, 2025)
The understanding of religious orientation and free will are two distinct concepts, yet both influences how individuals make decisions. However, there has been no clear identification of how religious orientation affects the understanding of free will in ethical decision-making and moral responsibility among theology students. The study aimed to analyze the relationship between religious orientation and the understanding of free will among theology students. The research employed a qualitative method with a phenomenological approach, and the primary data were analyzed using Braun and Clarke’s thematic analysis. The findings found out that religious orientation strongly influences theology students’ understanding of free will, as it serves as an ethical guide in decision-making. Faith, spiritual reflection, and personal experience also reinforce moral responsibility in the exercise of free will, affirming the close relationship between religious orientation and the understanding of free will.